Pragmatic Analysis of The Somatism “Heart” In “Anna Karenina” (Eurasian Research Bulletin, 2022)
This article is devoted to the pragmatic analysis of the somatism “heart” in “Anna Karenina” by Leo Tolstoy. This article reveals contextual meanings of the “heart” in different utterances. The findings are supported with the direct examples from the literary work